A very brief history of eternity - Eire, Carlos M. N. (Princeton : Princeton University Press, 2010)
Eire traces the concept of eternity from ancient times to the present. He examines the rise and fall of five different conceptions of eternity, how they developed, and how they have helped shape individual and collective self-understanding.
Big bang, big sleep, big problem -- Eternity conceived -- Eternity overflowing -- Eternity reformed -- From eternity to five-year plans -- Not here, not now, not ever.
Includes bibliographical references (p.[255]-258) and index.
Description based on print version record.
Keywords: Eternity -- History of doctrines; Civilization, Western; Electronic books